Neuregulin 4 Boosts the Efficacy of Anti-ERBB2 Neutralizing Antibodies - Miano, Carmen; Romaniello, Donatella; Mazzeschi, Martina; Morselli, Alessandra; Da Pra, Silvia; Sacchi, Francesca; Bongiovanni, Chiara; Sgarzi, Michela; Pantano, Elvira; Lauriola, Mattia; D’Uva, Gabriele (Frontiers in Oncology, 2022)
ERBB4 is a tyrosine kinase receptor reported to exert both oncogenic and tumor suppressor activities. These paradoxical effects were suggested to stem from different ERBB4 homo-/hetero-dimers and/or isoforms. By stratifying breast cancer patients for clinical and molecular subtypes and ERBB4 mRNA abundance, we here report that higher ERBB4 levels correlate with longer relapse-free survival in breast cancer patients of HER2-enriched and luminal A molecular subtypes, proposing a cancer-protecting role for this receptor in these specific subgroups. We also observed that HER2-enriched breast cancers express intermediate ERBB4 mRNA levels compared to luminal and triple-negative/basal-like subgroups, which displayed the highest and the lowest levels, respectively. Inspired by these clinical data, we tested the activation of ERBB4 by Neuregulins as a potential anticancer strategy for HER2+ breast cancers. To this end, we employed two HER2+ breast cancer cellular models (BT474 and SKBR3), which express intermediate/high and low ERBB4 levels, respectively. Cell proliferation and motility were evaluated on these cellular models following treatments with Neuregulin 1 (NRG1), which activates both ERBB3 and ERBB4, or Neuregulin 4 (NRG4), which specifically activates ERBB4. Both NRG1 and NRG4 were used alone or in combination with anti-ERBB2 neutralizing antibodies, namely trastuzumab and pertuzumab. In vitro treatment with NRG1 on BT474 cells restrained cell growth and reduced the anti-proliferative efficacy of trastuzumab. In contrast, treatment with NRG1 to SKBR3 cells increased cell proliferation and migration, and partially or completely impaired the anti-proliferative/anti-migratory action of trastuzumab and/or pertuzumab. Importantly, in both cell lines, treatment with NRG4 robustly potentiated the anti-proliferative action of trastuzumab and pertuzumab. Collectively, our data in HER2+ breast cancer cells highlight that NRG1 may exert both pro- and anti-proliferative effects, and may reduce the efficacy of anti-HER2 agents, whereas NRG4 may boost the anti-proliferative effects of anti-ERBB2 agents. We propose a provocative paradigm shift in the field of growth factors in cancer progression, suggesting the administration of ERBB4 ligands, such as Neuregulin 4, as a strategy to improve the efficacy of anti-ERBB2 agents.